The development of sex education training course through cooperative learning technique of undergraduate students at Institute of Physical Education - ขี่ทอง ชบา; มาลารัตน์ อนันต์; หุ่นนิรันดร์ พรสุข (Disease Control Journal, 2016)
The purposes of research and development were (1) to study the state of problem and the needs for the development of sex education training course for the undergraduate students at Institute of Physical Education. The samples were 17 lecturers who had taught Sex Education course, 17 administrators, and 392 undergraduate students. The research instruments were composed of semi-structured interview and survey of needs. For data analysis, Mean, standard deviation, and content analysis were used; (2) to create curriculum of training course for sex education through cooperative learning technique of undergraduate students at Institute of Physical Education. The samples were 6 experts and 30 undergraduate students. The research tools comprised the curriculum and the manual of training course, skills assessment form, sex education test, attitudes evaluation form towards sex education, satisfaction evaluation form with training course curriculum, and curriculum appropriateness evaluation form. For data analysis, Mean comparing with the criterion of average, Item content validity: I-CVI, S-CVI, Difficulty, discrimination, and reliability were utilized; (3) to try out and evaluate the results of training course curriculum on sex education through cooperative learning technique of undergraduate students at Institute of Physical Education in the pilot experimental group and the actual situation group. The research instruments were made up of the curriculum and the manual of training course, skills assessment form, sex education test, attitudes evaluation form towards sex education, satisfaction evaluation form with training course curriculum. For data analysis, percentage, Mean, standard deviation, dependent sample t-test, one-sample t-test, and Effectiveness Index: E.I. were used. The findings were found that the state of instructional management for sex education course taught in Institute of Physical Education, most lecturers taught this course according to the course syllabus and they focused on teaching by the lecture. The found problems were that undergraduate students paid less attention to the lecture; the place for studying was not favorable; it lacked media and technology and there were other activities, resulting in a decline of time for the instruction. As for the content, it was found that undergraduate students, lecturers, and administrators needed the aspect of similar content. Cooperative learning technique was used in the constructed curriculum which included 9 elements as follows; (1) Principle of curriculum, (2) Objective of curriculum, (3) Time period of training course, (4) Qualification and number of the trainees, (5) Training course media, (6) Results evaluation of training course, (7) Structure of curriculum, (8) Schedule of training course, and (9) Guidelines for organizing the training course activities. When the curriculum was tried out for the pilot experiment and the actual situation experiment, it was found that there was significantly an increase in both groups’ knowledge of sex education, in their attitudes towards sex education and in their skills needed to learn about sex education at the .05 level. In addition, their satisfaction with the training course curriculum was significantly higher than that of the set criteria, and there was Effectiveness Index value of knowledge in each group at 0.2887 and 0.3692 respectively.